Analysis of the Implementation of Musyarakah Financing Based on the Standard Book of Musyarakah Products: Analisis Implementasi Pembiayaan Musyarakah Berdasarkan Buku Standar Produk Musyarakah - Badruzzaman, Azzam; Latifah, Fitri Nur (Indonesian Journal of Innovation Studies, 2021)
The musyarakah financing product is a competitive flagship product of Sharia Rural Banks (BPRS) which has not experienced growth like other financing products. The lack of development of musyarakah financing products has caused BPRS to have more products based on fixed income financing which is similar to the conventional pattern that uses a fixed income structure. PT. BPRS Baktimakmur Indah is the largest BPRS with assets of Rp. 163,147,899,000 and the financing provided to the community reaches Rp. 126,807,530 as of December 31, 2019. This research was conducted at BPRS Baktimakmur Indah Branch throughout Sidoarjo which is located at Jln. Raya Bebekan No.21 Throughout the Taman District, Sidoarjo Regency. The purpose of this study was to analyze the implementation of musyarakah financing based on the standard book of musyarakah products published by the financial services authority. By using qualitative research methods through a phenomenological paradigm approach that requires researching a natural setting, with observation data collection techniques, direct interviews and literature from companies to support data needs. After the research was carried out, it was found that the BPRS Baktimakmur Indah branch of the Panjang branch had implemented musyarakah financing in accordance with the standard book of musyarakah products issued by the financial services authority.